2020
DOI: 10.1002/cam4.2933
|View full text |Cite
|
Sign up to set email alerts
|

Sequential boost of intensity‐modulated radiotherapy with chemotherapy for inoperable esophageal squamous cell carcinoma: A prospective phase II study

Abstract: Purpose: This prospective phase II study aimed to determine the efficacy and tolerability of sequential boost of intensity-modulated radiation therapy (IMRT) with chemotherapy for patients with inoperable esophageal squamous cell carcinoma (ESCC). Methods: Patients with histologically or cytologically proven inoperable ESCC were enrolled in this study (ChiCTR-OIC-17010485). A larger target volume for subclinical lesion was irradiated with 50 Gy, and then, a smaller target volume only including gross tumor was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The benefits of intensity-modulated radiotherapy (IMRT) over standard radiotherapy (RT), including decreased acute and late toxicities, improved quality of life, and opportunities for dose escalation, have been demonstrated in many disease sites. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] As a result, IMRT is often the preferred modality for radiotherapy delivery. The implementation of IMRT can be more resource-intensive than standard three-dimensional conformal RT (3DCRT), requiring insurance prior authorization, complex treatment planning, and specialized medical physics and dosimetry support.…”
Section: Racial and Ethnic Health Disparities In Delay To Initiation ...mentioning
confidence: 99%
“…The benefits of intensity-modulated radiotherapy (IMRT) over standard radiotherapy (RT), including decreased acute and late toxicities, improved quality of life, and opportunities for dose escalation, have been demonstrated in many disease sites. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] As a result, IMRT is often the preferred modality for radiotherapy delivery. The implementation of IMRT can be more resource-intensive than standard three-dimensional conformal RT (3DCRT), requiring insurance prior authorization, complex treatment planning, and specialized medical physics and dosimetry support.…”
Section: Racial and Ethnic Health Disparities In Delay To Initiation ...mentioning
confidence: 99%
“…Definitive chemoradiotherapy currently remains a treatment option for these patients who can to tolerate chemoradiation. Definitive chemoradiotherapy treatment options for ESCC include concurrent chemoradiotherapy (CCRT) ( 8 ), concurrent chemoradiotherapy followed by consolidation chemotherapy (CCRT-C) ( 9 11 ), induction chemotherapy followed by concurrent chemoradiotherapy (I-CCRT) ( 12 , 13 ), and sequential chemoradiotherapy (SCRT) ( 14 ). Studies have demonstrated that CCRT confers a survival benefit for locally advanced ESCC compared with SCRT ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 , 8 , 9 , 10 Cisplatin plus fluorouracil (PF) has become the conventional chemotherapy regimen since the RTOG85‐01 clinical trial. 6 However, toxicity limits the completion of concurrent chemotherapy, 11 and the disease failure rates remain high, necessitating more effective regimens. Several protocols have been explored, including fluorouracil plus leucovorin and oxaliplatin (FOLFOX), paclitaxel and fluorouracil (TF), and paclitaxel and carboplatin (TC) schemes, which did not show significant survival benefits.…”
Section: Introductionmentioning
confidence: 99%